The place and value of the human advisor in relation to generative AI in the provision of advice and feedback to students’ academic writing - Campitelli, Stephen Thomas (Journal of Academic Language and Learning, 2026)
In 2022, a challenge to a core Academic Skills Advisor (ASA) role, the individual consultation (1-1), emerged in the form of Chat GPT, a generative AI (gen AI) platform that can perform a similar role to that of the ASA in the provision of feedback and advice on students’ written academic work in 1-1 contexts. Some views hold that gen AI platforms can perform this role as well as an ASA, representing an equally capable and economically more feasible option. This paper examines this proposition by first considering the advantages gen AI brings to the 1-1 writing advising context before exploring the comparative advantages of the human advisor through the lens of a humanistic Personal – Pedagogical – Institutional framework. The paper concludes that human advisors offer many clear advantages over gen AI platforms in the 1-1 context working collaboratively with students’ academic writing, not the least of which is a crucial affective element. ASAs enact this by being actively co-present with students in the 1-1 role through dialogic, mutually recognitive advising which, in turn, has a referred, wider application.